The Emotional Labour of Public Library Work - Rodger, Joanne; Erickson, Norene (Partnership, 2021)
This study seeks to extend the research on the emotional labour of public library workers. Because emotional labour is a relatively new concept in library and information science research, researchers and practitioners need to better understand the emotional labour experiences of front-line workers in public libraries. A qualitative survey was distributed electronically to library workers in one Canadian province. Participants described meaningful experiences connecting with customers, but also identified major challenges in performing customer service work. Results showed that the public facing display of regulated emotions that is ingrained in library customer service training often conflicts with inner emotions. The inability to reconcile opposing emotions and perceived limited administrative support affects individual enjoyment of work and their personal well-being. Participants report exhaustion and burnout as outcomes of emotional labour. Library organizations must acknowledge the emotional labour aspect of library customer service work and provide more extensive formalized support for staff who are in customer service roles. Equipping staff with stronger emotional labour strategies might also help to build resilience and increase job satisfaction.